Pengaruh Influencer Marketing, Perceived Quality, dan Bundling Product terhadap Keputusan Pembelian Produk Daviena Skincare di Tiktokshop (Studi pada pengguna Tiktok) - Adilah Nur Fadilah; Rama Chandra Jaya (eCo-Buss, 2024)
The ultimate goal of this research is to assess the level of impact of Influencer Marketing, Perceived Quality and Bundling Product on Purchasing Decisions. The approach used is quantitative using a test sample of 100 sources. The results of this observation state that Influencer Marketing causes purchasing decisions and sig score 0.000 < 0.05 then t score of 8.559 > t distribution table 1.985. The Perceived Quality causes purchasing decisions and sig score 0.031 < 0.05 then t score of 2.193 > t distribution table 1.985. The Bundling Product causes purchasing decisions and sig score of 0.035 < 0.05 then t score of 2.134 > t distribution table 1.985. And simultaneously F count 103.231 > F distribution table 2.47 along with relevant scales of 0.000 < 0.05. This condition proves that the Influencer Marketing, Perceived Quality, and Product Bundling causes purchasing decisions. The squared correlation coefficient score in this research is 0.763 or 76.3% and 23.7% are other components not analyzed in this research.